New Exemptions to Anti-Circumvention Rules. - Samuelson, Pamela (Communications of the ACM, 2016)
The author reflects on the proposed exemptions to the anti-circumvention rules for technical protection measures (TPMs) used by copyright owners. Topics covered include exemptions already granted and suspended by the U.S. Copyright Office, the implications of the anti-circumvention rules beyond anti-piracy purposes, and details relating to the unlocking and jailbreaking exemptions. She discusses the effect of anti-circumvention rules on computer security testing.